Stroke transcranial Doppler in children with human immunodeficiency virus. (8th January 2020) - Dlamini, Nomazulu; Pohl, Keith; Eley, Brian; Van Toorn, Ronald; Kilborn, Tracy; Padayachee, Soundrie; Pontigon, Ann‐Marie; Kirkham, Fenella J; Wilmshurst, Jo
Abstract : Aims: To describe stroke syndromes and transcranial Doppler (TCD) findings in children with human immunodeficiency virus (HIV) and examine the associations between TCD and clinical and laboratory data. Method: We enrolled 42 children (24 males, 18 females) with HIV (median age=7y 6mo; 2y 7mo–15y 6mo), with and without stroke who underwent a TCD examination of the anterior and posterior circulations to derive time‐averaged maximum mean velocity (TAMMV) measurements for comparison with previous studies. Clinical and laboratory variables were extracted from the medical records. Results: Of the 42 children with HIV, five had right‐sided hemiparesis, three had chronic lung disease, two occurred post‐varicella infection, one after herpetic oral ulceration, and one had a poorly functioning left ventricle. Neuroimaging showed middle cerebral artery (MCA) TAMMV greater than 200cm/s, moyamoya‐like arteriopathy, left basal ganglia infarction with ipsilateral stenosis, hygroma consistent with venous thrombosis, and a hyperdense left MCA. Eight neurologically asymptomatic children had atypical TCD. The CD4 cell count was non‐significantly lower in 6 out of 30 children with atypical TCD (median=21.5; interquartile range=16.1–26.5) compared with the remainder (median=29; interquartile range=21.3–35.0; p =0.09). Interpretation: A variety of stroke syndromes occur in children with HIV. TCD suggests atypical intracranial vessels and/or haemodynamics in some children with HIV infection, consistent with vasculopathy, possibly related directly to immunodeficiency and/or infection. What this paper adds: A range of stroke syndromes are found in children with human immunodeficiency virus (HIV). Transcranial Doppler (TCD) velocities in HIV are commonly outside the range for typically developing children. TCD and neuroimaging data in children with HIV suggest intracranial vasculopathy as one mechanism for stroke. CD4 cell count is non‐significantly lower in children with HIV and atypical TCD. What this paper adds: A range of stroke syndromes are found in children with human immunodeficiency virus (HIV). Transcranial Doppler (TCD) velocities in HIV are commonly outside the range for typically developing children. TCD and neuroimaging data in children with HIV suggest intracranial vasculopathy as one mechanism for stroke. CD4 cell count is non‐significantly lower in children with HIV and atypical TCD. This article is commented on by Benjamin on page 667 of this issue. Video Podcast: https://youtu.be/PzBm2dK3Mpk